Modelling and design of improved powertrain solutions for electric and hybrid buses. Issue 4 (1st December 2017) - Ceraolo, Massimo; Giglioli, Romano; Lutzemberger, Giovanni; Pede, Giovanni
Abstract : There is a growing interest worldwide in reducing pollution and CO2 emissions from transportation field. Indeed, in recent years bus manufacturers have developed hybrid and electric versions of their products. In this regard, this study shows through a structured methodology how to model and design powertrains for pure electric and series‐hybrid buses. First step is aimed to define a simulation model of the existing bus, experimentally validated, and then modelling and design of pure electric and hybrid powertrains. After analysing main drawbacks of pure electric vehicles fed by large and heavy batteries, and hybrid vehicles fed by diesel fuel, alternative solutions have been considered. In particular, different fuels, i.e. compressed natural or liquefied natural gas, have been analysed for the hybrid version, while a pure electric vehicle equipped with a reduced storage system able to be quickly recharged at bus stops has been introduced. In all the considered cases, particular attention has concerned the sizing of the electrochemical storage.